Modeling Ca2+ signals - Friel, David (Henry Stewart Talks, 2007)
Introduction to quantitative descriptions of Calcium signaling, Examples of Calcium signals in sympathetic neurons, Steps in constructing Calcium signaling models, Qualitative properties of Calcium dynamics, Methods for quantifying Calcium handling in intact cells, Analysis of Calcium dynamics in sympathetic neurons
Archived at 2021/02/25